The Confidence Game in American Literature - Wadlington, Warwick, 1938- (Book collections on Project MUSE., 1975)
Drawing on modern studies of rhetoric and the concept of the Trickster, the author examines Herman Melville, Mark Twain, and Nathanael West as creators of a fictive experience centered in deceptive or problematic transactions of confidence. The model of a confidence game, suggested by the writers' own thematic preoccupations, permits an analysis of the social motivations inherent in the fiction. The author concentrates on the process by which confidence is established and the ways in which deception leads to regeneration and an altered perception of authority. His approach increases our unde.